JENIS JENIS INSTRUMEN DALAM EVALUASI PEMBELAJARAN - HUMAIROH; MUHAMAD NURFAHBIANSYAH; FITRI HILMIYATI; ENUNG NUGRAHA (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Learning evaluation is a crucial component in the educational process to measure the success of students in achieving learning objectives. The quality of evaluation results heavily depends on the instruments used. Therefore, this paper aims to analyze various types of learning evaluation instruments and explain their development procedures to improve the quality of education. The method used is a literature study by reviewing various sources, including journals and other relevant scientific references. The research results show that learning assessment instruments are divided into two main categories, namely test instruments and non-test instruments. Test instruments, such as written tests, oral tests, and performance tasks, focus on measuring cognitive aspects. Meanwhile, non-test instruments, such as observation, interviews, questionnaires, and portfolios, are used to assess students' affective and psychomotor aspects. The proper and valid use of instruments is key to obtaining accurate and comprehensive data on students' learning progress. This paper concludes that the development of valid and reliable evaluation instruments requires systematic procedures, starting from the preparation of blueprints, item writing, to trial tests and result analysis. The use of diverse and high-quality instruments can provide more effective feedback for teachers to improve teaching strategies and, ultimately, encourage the overall enhancement of learning quality.